CONTROL SYSTEM ENGINEERING: PRINCIPLES AND DESIGN - Zamri Omar (Penerbit UTHM, 2015)
The study of control system engineering is essential for mechanical, aerospace and electrical engineering students. This book presents an elementary treatment to the concept and design of control systems engineering. It is suitable to be used as a text for senior students pursuing diploma or bachelor degree, and as essential compact reference for postgraduate students. This book is also for anyone who desires to know the fundamental of control systems engineering.